2016
DOI: 10.1089/jwh.2015.5390
|View full text |Cite
|
Sign up to set email alerts
|

A New Way to Estimate the Potential Unmet Need for Infertility Services Among Women in the United States

Abstract: Background: Fewer than 50% of women who meet the medical/behavioral criteria for infertility receive medical services. Estimating the number of women who both meet the medical/behavioral criteria for infertility and who have pro-conception attitudes will allow for better estimates of the potential need and unmet need for infertility services in the United States. Methods: The National Survey of Fertility Barriers was administered by telephone to a probability sample of 4,712 women in the United States. The sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Because most infertility clinic patients are White and middle class, much of what we know of infertility causes and consequences has been shaped by samples of White, middle‐class people with infertility (Bell, ). Population data provide evidence that both infertility prevalence and infertility treatment in the United States are stratified by socioeconomic status and race/ethnicity: Those with higher incomes, private insurance, and who are White have more support and access to treatment than others (Greil, Slauson‐Blevins, et al, ). Yet regardless of socioeconomic status and race/ethnicity, women who experience infertility report greater desire to have children and want more children than women who have not experienced infertility (Shreffler et al, ).…”
Section: Education and Awareness Of Reproduction And Infertility Treamentioning
confidence: 99%
See 1 more Smart Citation
“…Because most infertility clinic patients are White and middle class, much of what we know of infertility causes and consequences has been shaped by samples of White, middle‐class people with infertility (Bell, ). Population data provide evidence that both infertility prevalence and infertility treatment in the United States are stratified by socioeconomic status and race/ethnicity: Those with higher incomes, private insurance, and who are White have more support and access to treatment than others (Greil, Slauson‐Blevins, et al, ). Yet regardless of socioeconomic status and race/ethnicity, women who experience infertility report greater desire to have children and want more children than women who have not experienced infertility (Shreffler et al, ).…”
Section: Education and Awareness Of Reproduction And Infertility Treamentioning
confidence: 99%
“…The study of infertility was initially primarily limited to the study of clinic patients, but once research moved beyond treatment seekers to include a focus on women with infertility who were not seeking treatment, it became clear that there is considerable diversity among those who meet the criteria for infertility. The diversity of experiences with infertility, particularly among those not seeking medical treatment, raises important questions about the social dimensions of the experience of infertility, the process of self-identifying as infertile, and the challenges involved in estimating the unmet need for infertility counseling and treatment (Greil, Slauson-Blevins, Tiemeyer, McQuillan, & Shreffler, 2016).…”
Section: Definitions Of Infertilitymentioning
confidence: 99%
“…The Cap-Score™ has the potential to change the management of male factor infertility and infertility of unknown origin by increasing access, improving outcomes, and saving money. Given the substantial unmet need for infertility treatment in the USA—over 50% of the need for fertility treatment is unmet [ 29 , 30 ], and just over 60% of nulliparous women in the USA with current fertility problems have ever used infertility services [ 4 ]—the Cap-Score™ is a potential avenue for increased access. Increased access to ART will likely result due to cost savings.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, much of this work emanated from a more interpretivist social science tradition, drawing on primarily qualitative methods of inquiry. Exceptions here include quantitative analyses of incidence/prevalence and unmet need for treatment (Frank 1983;Larsen 1994;Morgan 1991;Boivin et al 2007), as well as a series of more recent studies documenting perception of infertility as a problem (Greil et al , 2011(Greil et al , 2016; Johnson and Fledderjohann 2012) and patterns of medical help-seeking (Greil and McQuillan 2004;Stephen and Chandra 2000;White et al 2006). Even though fertility and infertility research tend to use different methods and epistemologies, both are incorporating new approaches over time.…”
Section: Fields and Frameworkmentioning
confidence: 99%
“…In their study of infertility service use and unmet need using the National Survey of Family Growth, Stephen and Chandra (2000, p. 133) classified partnered women as "infertile" based on the 12-month medical definition but noted that this was imperfect because they could not account for certain "social bases to infertility […] the desire to become pregnant […]." Greil et al (2016) showed that adding the requirement that medically infertile women desire to have a child reduces estimated need for infertility services by 15.9%.…”
Section: Fertility Attitudes and Intentionsmentioning
confidence: 99%